Analisis Faktor-Faktor yang Mempengaruhi Pengungkapan Islamic Social Reporting pada Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2010-2013 - Tantri Puji Rahayu; Agung Budi S. (UPT Penerbitan Universitas Jember, 2018)
Islamic Social Reporting (ISR) is a social responsibility disclosure index that has specific indicators on ethical principles of Islam. In this study, assessment a level of ISR disclosure performed among list of Jakarta Islamic Index companies. The aim of this study is to obtain an empirical evidence about factor that affect Islamic Social Reporting (ISR) in company’s annual report. The factors that used in this study such as:social activity, industry size, profitability, and environmental performance. Measurement of Islamic Social Reporting is based on islamic social reporting categories that used to calculate the Islamic Social Reporting Index as seen from the company’s annual report. This research is a quantitative research. The population of this research are all companies that listed in Jakarta Islamic Index totaling 30 companies. Sampling technique used purposive sampling technique. Total sample was 8 companies. The analytical techniques was conducted by multiple regression method and also classical assumption test. The results of this study indicate that the industry size significantly positive influence the Islamic Social Reporting (ISR) disclosure. Meanwhile, profitability and environmental performance had no significant effect to the Islamic Social Reporting (ISR) disclosure in Indonesia.Keywords: Islamic Social Reporting, Jakarta Islamic Index industry size, profitability, and environmental performance.